Japanese Immigrants In Sarawak Before World War Two: Assimilation Through Inter-Ethnic Marriages - Md Akhir, Md Nasrudin; Govindasamy, Geetha; Paidi, Rohayati (WILAYAH: The International Journal of East Asian Studies, 2021)
Abstract: The arrival of Japanese immigrants, especially karayuki-san, traders, and farmers in Sarawak between the 1880s and1940s, has rarely been given sufficient attention by scholars. For the most part, not only did the Japanese immigrants successfully integrate into the economic eco-system, but they also assimilated with the locals through inter-marriages. Archival records, primarily obtained from the Sarawak State Archives, suggests that families of inter-ethnic marriages went through a life of hardship, especially when Japanese spouses or relatives were imprisoned in the internment camps soon after World War Two ended. For the most part, the research mainly focuses on Seiji Kuno or otherwise known as Mohamed Towpik Kuno, who married a local Malay woman and embraced Islam. The life of Kuno depicts the extent to which a Japanese immigrant became absorbed into the dominant culture of the mainstream Sarawak society. Kuno’s general attitude towards the local society, his service to the community in various capacities, his attitude towards political matters and finally, his religious inclination showcased the extent to which assimilation had taken place voluntarily. Apart from Kuno, the research also examines other personalities’ lives, like Sunao Miyaji, who was married to Lamah Binti Bakar, and Maria Osaichi and Oasa, who were Japanese immigrants married to Chinese Sarawakians. It is against this background that this research argues that marriages between Japanese immigrants and locals in Sarawak before World War Two was indeed a cause for further assimilation into the host culture between spouses, family members and the broader community. At the same time, the research posits that cemeteries involving Japanese immigrants should be promoted as tourist destinations as they reflect Sarawak’s rich multicultural heritage and history of assimilation with foreigners.